2021
DOI: 10.3390/ijerph18062813
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Korean Fencing Club Members’ Participation Intention Using the TPB Model

Abstract: This study aims to investigate effects of three factors from the Theory of Planned Behavior (TPB)—attitude, subjective norms, and perceived behavioral control—on 233 fencing club members’ intention to continue participation, while considering fencing’s low popularity as a sport in Korea. This study analyzed data from members of fencing clubs in Seoul, Gyeonggi, Daegu, and Busan, using frequency analysis, exploratory factor analysis, reliability analysis, correlational analysis, and multiple regression with SPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…Such a high level of emotional awareness positively influences the extent to which members consider important people to support their participation in Furthermore, the results validated that attitudes toward martial arts, subjective norms, and martial arts attachment all had positive and significant effects on the intention to participate in martial arts. These three direct effects were found to be consistent with the results of previous research on the TPB, Kim and Kim (2021), Huang et al (2022), and attachment-related research, Jin et al (2020), respectively. In other words, martial arts group members' evaluation of martial arts, the extent to which members consider important people to support their participation in social media activities, and the strength of their emotional connection to the marketing and promotional content of the community positively influenced their intention to participate in martial arts.…”
Section: Academic Findings and Contributionssupporting
confidence: 89%
See 1 more Smart Citation
“…Such a high level of emotional awareness positively influences the extent to which members consider important people to support their participation in Furthermore, the results validated that attitudes toward martial arts, subjective norms, and martial arts attachment all had positive and significant effects on the intention to participate in martial arts. These three direct effects were found to be consistent with the results of previous research on the TPB, Kim and Kim (2021), Huang et al (2022), and attachment-related research, Jin et al (2020), respectively. In other words, martial arts group members' evaluation of martial arts, the extent to which members consider important people to support their participation in social media activities, and the strength of their emotional connection to the marketing and promotional content of the community positively influenced their intention to participate in martial arts.…”
Section: Academic Findings and Contributionssupporting
confidence: 89%
“…H6: User experience will have a positive and significant effect on martial arts attachment. Kim and Kim (2021) investigated the effect of attitude and subjective norms on members' intention to continue participating in a fencing club in South Korea. The results indicated that attitudes and subjective norms had a positive and significant effect on the intention to continue participation.…”
Section: User Experiencementioning
confidence: 99%
“…In addition, we included Ho et al's (2017) descriptive norms scale (consisting of three items) [33,34]. Additionally, we used Young-Jae Kim and E-Sack Kim's (2021) perceived behavioral control scale (consisting of four items) [35] . Finally, we adapted Lim ' s (2017) corrective actions scale (consisting of five items) to the current research context.…”
Section: Measurementioning
confidence: 99%
“…Perceived behavioral control to home-based exercise. For measuring PBC, we modified three items using a seven-point Likert scale (1=strongly disagree and 7=strongly agree) [35]. A higher score indicated strong PBC (M=4.61, SD=1.49, Cronbach's α=0.93).…”
Section: Measurementioning
confidence: 99%
“…Research has established that TPB is a strong, powerful theory for predicting individuals' intentions, and it is widely used in research fields regarding sports and physical activities [28,31]. Studies have used TPB to explain people's intention of participating in physical activities or a particular kind of sport, for example, college students in the UK [28] and fencing in Korea [31]. Therefore, we applied the theory of planned behaviour (TPB) as the theoretical framework in this study and explored the variables that predicted winter sports participation intention.…”
Section: Introductionmentioning
confidence: 99%